Benthic Macroinverteberate Composition and Diversity in The Mengkibol River , Kluang, Johor, Malaysia. - Aweng Eh Rak; Ahmad Abas; Ismid Said; Maketab Mohamed (2010)
The study was to identify the benthic macro-invertebrate species and compositions in the urban river ( Mengkibol River ) to be used as biological indicators for water quality assessment and also to determine the water quality factor that influence benthic organism compositions and distributions, the study was carried out in Mengkibol River, Kluang, Johor, Malaysia between November 2008 to August 2009. Two sampling points 500 meters apart were fixed by Global Positioning System (GPS). Temperature was found to be an important ecological factor, which influence distribution of benthic macro-invertebrate in the present study. In addition, conductivity was also found to be an important factor, in the distribution of benthic macro-invertebrate. DO, pH, and turbidity did not play any considerable role in benthic macro-invertebrate assemblage in this study. A total of 176 genus were identified and of these 148 genus belonged to insect order 23 genus to gastropoda (downstreams stations) .